Condition, length-weight relationship, sex ratio and gonadosomatic index of Indian Mackerel (Rastrelliger kanagurta) captured from Kuantan coastal water - Rahman, Mohammad Mustafizur; Hafzath, A. (Asian Network for Scientific Information, 2012)
This study describes the Condition factor, Length-Weight relationship, Gonadosomatic index and sex ratio of Indian mackerel (Rastrelliger kanagurta) which is an important fish in the Kuantan coastal water, Malaysia. Data were obtained from December 2011 to May 2012. A total of 1064 Indian mackerel specimens were studied for this research. Result showed that male was significantly more than female (χ2 = 7.91; P <0.01) in the Indian mackerel population in the Kuantan coastal area. Length-Weight relationship of each month was significant (P<0.01) with all coefficients of determination (R2) values being higher than 0.72. The allometric coefficients (b) of length-weight relationship varied between 2.5128 (April) and 3.0807 (May). A negative allometric growth of Indian mackerel was observed in January, March and April. An isometric growth was observed in December and February, while a positive allometric growth was observed only in May. The b-value of the of the length-weight relationship of Indian mackerel in April was very low compared to other month. The condition factor ranged from 1.0499 to 1.1320. Condition factor was significant different between months (P< 0.05). The significantly lowest mean condition factor was found in December and the highest in February and April. Overall higher mean condition factor was observed in smaller fish of both sex. Overall mean condition factor of female was better than male. Gonadosomatic index of Indian mackerel in February was higher than thouse observed in March and April and followed by May. Gonadosomatic index rapidly increased after January and reached at peak in February. After February gonadosomatic index was declining again. A positive relationship was observed between gonadosomatic index and condition factor of Indian mackerel. The peak spawning season of Indian mackerel in Kuantan coastal water was from February to April. The spawning season of Indian mackerel in Kuantan coastal water falls within the period between end of January and end of May.